2014
DOI: 10.1021/am505622c
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Porous MnO2 Microspheres Doped with Homogeneously Distributed Fe3O4 Nanoparticles for Supercapacitors

Abstract: Hierarchically porous yet densely packed MnO2 microspheres doped with Fe3O4 nanoparticles are synthesized via a one-step and low-cost ultrasound assisted method. The scalable synthesis is based on Fe(2+) and ultrasound assisted nucleation and growth at a constant temperature in a range of 25-70 °C. Single-crystalline Fe3O4 particles of 3-5 nm in diameter are homogeneously distributed throughout the spheres and none are on the surface. A systematic optimization of reaction parameters results in isolated, porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 39 publications
2
58
0
Order By: Relevance
“…One promising approach to improve their performance is to combine other metal oxides in a composite. Manganese dioxide (MnO 2 ) with favorable properties and high theoretical specific capacitance (1370 F g −1 ) makes it a promising electrode material in energy storage and conversion devices [26][27][28][29][30]. Furthermore, three-dimensional (3D) transitional metal oxides/ hydroxides nanostructures assembled from low-dimensional building blocks [31][32][33][34] exhibit enhanced properties compared to their bulk counterparts by offering a large specific surface area, high surface/body ratios, the enhanced permeability for the electrolyte ions, and rich electrochemically active sites [35].…”
Section: Introductionmentioning
confidence: 99%
“…One promising approach to improve their performance is to combine other metal oxides in a composite. Manganese dioxide (MnO 2 ) with favorable properties and high theoretical specific capacitance (1370 F g −1 ) makes it a promising electrode material in energy storage and conversion devices [26][27][28][29][30]. Furthermore, three-dimensional (3D) transitional metal oxides/ hydroxides nanostructures assembled from low-dimensional building blocks [31][32][33][34] exhibit enhanced properties compared to their bulk counterparts by offering a large specific surface area, high surface/body ratios, the enhanced permeability for the electrolyte ions, and rich electrochemically active sites [35].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal compounds with superior electrochemical characteristics have been widely used as supercapacitors electrode materials . MnO 2 is a promising candidate as an electrode material for supercapacitors because of its superior electrochemical performance, such as low cost and natural abundance . However, it's also reported that the performance of nanostructured MnO 2 as the electrode material in supercapacitors is unsatisfactory .…”
Section: Supercapacitorsmentioning
confidence: 99%
“…[146] MnO 2 is a promising candidate as an electrode material for supercapacitors because of its superior electrochemical performance, such as low cost and natural abundance. [147] However, it's also reported that the performance of nanostructured MnO 2 as the electrode material in supercapacitors is unsatisfactory. [148,149] In order to solve this problem, some composites were formed in the hope of enhancing the electrochemical performance.…”
Section: Metal Oxide-metal Molybdatesmentioning
confidence: 99%
“…Meng et al [137] fabricated hierarchically densely packed porous MnO 2 microspheres doped with Fe 3 O 4 NPs through a one-step low-cost ultrasound-assisted method. The SEM and TEM images (Fig.…”
Section: Composites Of Manganese Oxides and Other Tmosmentioning
confidence: 99%